Student’s learning: Instrumentally, Integratively or Personally Motivated? - Somariah Fitriani (Register Journal, 2017)
The study focuses on learners’ motivation to learn English as L2/foreign language. For data collection, questionnaire was distributed to 82 respondents of STIBA IEC Jakarta via whatsApp and face book messenger. In addition, interviews were also conducted to find out the detail information about the role of teacher and inspirational/motivational teacher. For data analysis, the step of sorting, classifying, coding, and presenting the data and drawing conclusion was adopted.  This is a research based article, which has aimed to elaborate the learners’ English learning motivation whether it is instrumentally, integratively or personally motivated and the most dominance type of motivation as well as the important role of teacher in motivating students. It is somewhat surprising that there are six categories found in the research, namely personal motivation (PS), integrative motivation (IT), instrumental motivation (IS), the combination of PS IT, PS IS, and IT IS. The findings have revealed that 1) instrumental motivation is the most dominant type as the first rank, which includes to get a better living, better jobs and position; PS IS as second rank, IT IS as the third rank, PS IT as the fourth rank, personal motivation as the fifth rank and integrative motivation as the last rank; 2) teacher who is resourceful, skillful, competent and has good personality plays a imperative role in motivating and inspiring students. To sum up, regardless of personal, integrative or instrumental motivation, teacher as a role model also determines learner’s success in learning L2.         Keywords: motivation, L2/foreign language learning, instrumental, integrative, personal motivation    INDONESIAN ABSTRACT Fokus kajian ini adalah motivasi peserta didik untuk mempelajari bahasa Inggris sebagai bahasa kedua atau bahasa asing. Untuk mengumpulkan data, daftar pertanyaan dibagikan kepada 82 responden STIBA IEC Jakarta pada semester terakhir melalui WhatsApp dan face book messenger. Selain itu, wawancara juga dilakukan untuk mengetahui informasi secara detail, terutama tentang peran guru dan guru yang inspirasional / motivasional. Untuk analisis data, tahap pemilahan, klasifikasi, pengkodean, dan penyajian data serta kesimpulan diadopsi. Ini adalah artikel berbasis penelitian, yang bertujuan untuk menguraikan motivasi belajar bahasa Inggris peserta didik baik secara instrumental, integratif atau motivasi pribadi dan jenis motivasi yang paling dominan serta peran penting guru dalam memotivasi siswa. Agak mengejutkan bahwa ada enam kategori yang ditemukan dalam penelitian ini yang berbeda dengan penemuan lainnya, yaitu motivasi personal (PS), motivasi integratif (IT), motivasi instrumental (IS), kombinasi PS IT, PS IS, dan IT IS. Temuan tersebut telah mengungkapkan bahwa 1) motivasi instrumental adalah jenis yang paling mendominasi sebagai peringkat pertama, yang mencakup alasan mendapatkan kehidupan, pekerjaan dan jabatan yang lebih baik; PS IS sebagai peringkat kedua, IT IS sebagai peringkat ketiga, PS IT sebagai peringkat keempat, motivasi pribadi sebagai peringkat kelima dan motivasi integratif sebagai rangking terakhir; 2) Guru yang cakap, terampil, kompeten dan memiliki kepribadian yang baik memainkan peran penting dalam memotivasi siswa. Singkatnya, terlepas dari motivasi pribadi, integratif atau instrumental, guru sebagai panutan juga menentukan keberhasilan peserta didik dalam belajar L2. Kata kunci: motivasi, pembelajaran bahasa kedua/bahasa asing, motivasi instrumental, integratif dan personal.